PERAN AYAH DALAM MEMBENTUK KARAKTER MANDIRI ANAK USIA 5-6 TAHUN - Sunniya, Nasywa Haniifa; Jayadinata, Asep Kurnia; Nurdiansyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Independence is an important character trait that needs to be instilled from an early age because it forms the basis for children's ability to make decisions, take responsibility, and face various life challenges. This study aims to understand the lived experiences of fathers in shaping the independent character of 5–6-year-old children in Group B of Al-Hikam Kindergarten, Purwakarta. The study used a qualitative method with a phenomenological design. The participants consisted of three fathers selected through a purposive sampling technique. Data were collected through semi-structured interviews and analyzed using the Colaizzi method. The results of the study revealed five main themes: fathers as important figures in shaping children's independence, fathers' emotional presence as a reinforcement of independence, providing space for exploration and decision-making, father-mother collaboration in parenting, and supporting and inhibiting factors in the development of independence. The research findings confirm that fathers' involvement through role models, emotional support, and providing opportunities for independent learning plays a significant role in shaping the independent character of early childhood children.